1995
DOI: 10.1111/j.1600-9657.1995.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Replantation of 400 avulsed permanent incisors. 1. Diagnosis of healing complications

Abstract: A material of 322 patients with 400 avulsed and replanted permanent teeth were followed prospectively in the period from 1965 to 1988 (mean observation period = 5.1 yrs). The age of the patients at the time of replantation ranged from 5 to 52 yrs (mean = 13.7 yrs and median = 11.0 yrs). Standardized patient records were used through the entire period in order to obtain valid data concerning the extent of injury and treatment provided. At the follow-up period, pulpal and periodontal healing were monitored by cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
304
1
24

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(339 citation statements)
references
References 20 publications
10
304
1
24
Order By: Relevance
“…[1][2][3][4] When treated with adequate indications, autotransplantation offers a fast and economically viable option for replacing missing teeth 2,[5][6][7] Root resorption, the most common complication accompanying autotransplantation, leads to poor esthetics, the tilting of adjacent teeth, loss of function, and permanent tooth loss. [8][9][10] Occurrence of replacement resorption is influenced by factors such as the extra-alveolar period 11 , preservative solution 12 , pulpal revascularization 13 , and microbial contamination. 14 Treatment, often complex, time-consuming, and expensive, requires a multidisciplinary approach including endodontic, periodontal, surgical, and orthodontic treatment, as well as esthetic coronal restoration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] When treated with adequate indications, autotransplantation offers a fast and economically viable option for replacing missing teeth 2,[5][6][7] Root resorption, the most common complication accompanying autotransplantation, leads to poor esthetics, the tilting of adjacent teeth, loss of function, and permanent tooth loss. [8][9][10] Occurrence of replacement resorption is influenced by factors such as the extra-alveolar period 11 , preservative solution 12 , pulpal revascularization 13 , and microbial contamination. 14 Treatment, often complex, time-consuming, and expensive, requires a multidisciplinary approach including endodontic, periodontal, surgical, and orthodontic treatment, as well as esthetic coronal restoration.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Occurrence of replacement resorption is influenced by factors such as the extra-alveolar period 11 , preservative solution 12 , pulpal revascularization 13 , and microbial contamination. 14 Treatment, often complex, time-consuming, and expensive, requires a multidisciplinary approach including endodontic, periodontal, surgical, and orthodontic treatment, as well as esthetic coronal restoration. 15 Root resorption may be transitory or progressive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andreasen et al (31,32) and Kling et al (33) showed excellent radiographic images of the ingrowth of bone and periodontal ligament (PDL) (next to the inner dentinal wall) into the canal space with arrested root formation after the replantation of avulsed maxillary incisors, suggesting a complete loss of the viability of pulp, apical papilla, and/or HERS. Some cases showed partial formation of the root accompanied with ingrowth of bone and PDL into the canal space, and in some cases the teeth continued to develop roots to their completion, suggesting that there was partial or total pulp survival after the replantation.…”
Section: The Potential Role Of Scap In Replantation and Transplantationmentioning
confidence: 99%
“…Nevertheless, despite these treatments, unsuccessful cases are still numerous, and after a mean period of 4 to 6 years, the teeth are ultimately lost (13). Thus, the search for new substances that may inhibit or delay the effects of root resorption and promote the repair in the space occupied by the periodontal ligament is essential.…”
Section: Introductionmentioning
confidence: 99%